The waste-to-energy concept - Shaik Abbas, Shaik Irshad Mikail; Ahmad Shauwal, Ahmad Aiman Hidayat; Azrul Amri, Nuramira Maisarah; Ahmad Kamaruddin, Afrina; Syed Hasbullah, Sharifah Nur Batrisyia; Mohammad, Noorita (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Malaysia is currently facing a serious problem with solid waste, especially in cities where landfill space is running out. Due to a lack of environmental understanding and concern, this country also struggles with improper trash disposal by people. This method breaks down biodegradable waste to produce methane gas, which can be used to generate electricity through a turbine. The research also suggests involving communities through small-scale biogas systems, and awareness campaigns. This approach helps reduce pollution, manage waste better, and supports Malaysia’s goal of becoming more sustainable.